A Study of Training Preferences in Rice Cultivation in Jammu District of J&K State - Yogesh Kumar; M. S. Nain (Indian Journal of Extension Education, 2013)
Ever increasing population poses production needs of 140 million tonnes of rice per year by 2025 requiring higher management practices. This demands increased emphasis on need based training of farmers in rice production technology. The present study was undertaken in Jammu district of J&K state to delineate the farmers’ training need in rice production. The study was conducted on 80 randomly selected farmers of R.S. Pura block with a pre-structured interview schedule. The findings revealed that the farmers were requiring training in almost all the subject matter areas of rice production specially use of insecticides, pesticides, use of manures and fertilizers, seed and seed technology and water management.